On Hopf algebras over the unique 12-dimensional Hopf algebra without the dual Chevalley property. Issue 4 (3rd April 2019) - Xiong, Rongchuan
Abstract: Let k be an algebraically closed field of characteristic zero. We determine all finite-dimensional Hopf algebras over k whose Hopf coradical is isomorphic to the unique 12-dimensional Hopf algebra C without the dual Chevalley property, such that the diagrams are strictly graded and the corresponding infinitesimal braidings are indecomposable objects in C C Y D . In particular, we obtain new Nichols algebras of dimension 18 and 36 and two families of new Hopf algebras of dimension 216.